Pedagogical Competence of Civic Education Teacher in 21st Century: A Systematic Literature Review - Kabatiah, Maryatun; Batubara, Abdinur; Ramadhan, Taufiq; Rachman, Fazli (Jurnal Kewarganegaraan, 2024)
AbstractThe objective of this study is to ascertain the standards for pedagogical proficiency among civic education teacher in the 21st century, as well as to identify approaches for enhancing their competency. The research method chosen is the Systematic Literature Review (SLR), which uses data from international and national journal articles. The findings indicate that (1) the essential competencies that Civic Education Teachers in the 21st century must possess include life and career skills, encompassing self-regulation, social interaction, and a culture of leadership, productivity, and responsibility; (2) The acquisition of learning and innovation skills, encompassing critical thinking, problem-solving abilities, effective communication, and collaborative engagement in creative endeavors and information sharing; (3) The acquisition of skills in information media and technology, encompassing both information technology and media abilities, is of paramount importance. Teachers must have a comprehensive understanding of information literacy, media literacy, and ICT literacy. Digital pedagogy is a strategy to improve the competence of 21st-century PPKn teachers. Digital pedagogy presents not only digital learning but also digital ethics in utilizing digital resources or learning media.---------------------------------------Abstrak Penelitian menelaah standar kemahiran pedagogi di kalangan guru PPKn pada abad ke-21, serta mengidentifikasi pendekatan untuk meningkatkan kompetensi mereka. Metode penelitian yang dipilih adalah Systematic Literature Review (SLR) dengan sumber data terdiri dari gabungan artikel jurnal internasional dan nasional. Temuan menunjukkan bahwa: (1) kompetensi esensial yang harus dimiliki guru di abad 21 meliputi keterampilan hidup dan karir, meliputi pengaturan diri, interaksi sosial, dan budaya kepemimpinan, produktivitas, dan tanggung jawab, (2) perolehan keterampilan belajar dan inovasi, yang mencakup pemikiran kritis, kemampuan memecahkan masalah, komunikasi efektif, dan keterlibatan kolaboratif dalam upaya kreatif dan berbagi informasi, (3) perolehan keterampilan dalam media dan teknologi informasi, yang mencakup kemampuan teknologi informasi dan media, adalah hal yang sangat penting. Urgen bagi guru untuk memiliki pemahaman komprehensif tentang literasi informasi, literasi media, dan literasi TIK. Pedagogi digital hadir sebagai strategi upaya peningkatan kompetensi guru PPKn abad 21. Pedagogi digital tidak hanya menghadirkan pembelajaran digital, tetapi juga etika digital dalam menamfaatkan sumber daya atau sebagai media pembelajaran digital.
Keywords: Pedagogical Competence; 21st-century; Learning; Civic Education; Kompetensi Pedagogi; Abad 21; Pembelajaraan; Pendidikan Kewarganegaraan.